Judicial Discretion in Determining the Quantum of Nafkah Māḍiyah (A Study of Banda Aceh Syar’iyah Court Decisions) - Arrayansyah, Faisal; Mukdin, Khairani; Alimuddin (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2025)
This study aims to analyze judicial discretion in determining the quantum of nafkah māḍiyah (past maintenance) in divorce cases at the Banda Aceh Syar’iyah Court through nine decisions issued between 2020 and 2025. The primary issue identified is the absence of standardized benchmarks or technical guidelines, leading to disparities among decisions even when trial facts are relatively similar. This study employs a juridical-normative-empirical research method, utilizing both case and statutory approaches. It applies content analysis of decisions and interview methods, examined through the perspectives of Islamic law (mazhab Shafi'i), substantive justice theory, and qaidah fiqhiyah (legal maxims). The findings indicate that judges continue to exercise individual discretion based on trial facts, resulting in variations where claims are granted fully, partially, or rejected entirely. The basis for calculation and legal reasoning is often not elaborated in detail; consequently, substantive justice is not always reflected in the decisions. From the perspective of Islamic law, particularly the Shafi'i school of thought, nafkah māḍiyah is obligatory provided the wife is not nusyūz, with consideration given to the wife's reasonable needs and the husband's capacity; however, the practical application remains inconsistent. This study offers theoretical implications by strengthening the application of substantive justice in the religious judiciary and demonstrating that judicial discretion can serve as an instrument of justice provided it balances formal legal, moral, and social aspects. Practically and in terms of policy, it is recommended that the Syar’iyah Court formulate technical guidelines for determining nafkah māḍiyah based on Shafi'i fiqh and principles of substantive justice to ensure decisions are legally valid and socially just.